Effectiveness of a chlorhexidine dentifrice in orthodontic patients: a randomized-controlled trial - K. P. K. Olympio (journal of clinical periodontology, 2006)
This blind and randomized-controlled trial analysed chlorhexidine dentifrices in relation to dental plaque, gingivitis, bleeding, calculus and enamel extrinsic staining development. Volunteers in fixed orthodontic therapy used the following dentifrices: 1100 ppmF, NaF (group A, n527); experimental, 1100 ppmF, NaF and chlorhexidine 0.95% (group B, n528); and experimental, chlorhexidine 0.95% (group C, n528). At baseline, after 6, 12 and 24 weeks, clinical examinations were carried out. The gingivitis, bleeding and plaque data were tested by ANOVA and Tukey’s post hoc tests. Stain and calculus data were analysed by Kruskal–Wallis and Dunn’s post hoc tests (po0.05). Plaque, gingivitis and bleeding scores improved in all three groups, but up to the 6 and 12 weeks examination the products containing chlorhexidine were statistically better. The chlorhexidine dentifrices significantly increased the mean of the stain index, although most of the patients did not notice the stains. The calculus index was not significantly modified. In summary, this study suggests that the use of dentifrices containing chlorhexidine seems to be effective for the treatment of gingivitis in orthodontic patients, although the intense motivating contact that the volunteers had with the researchers may have also played a role.